Canine Macrophage DH82 Cell Line As a Model to Study Susceptibility to Trypanosoma cruzi Infection - Mendonça, Pedro Henrique Braz; Rocha, Raphael Francisco Dutra Barbosa da; Moraes, Julliane Brito de Braz; LaRocque-de-Freitas, Isabel Ferreira; Logullo, Jorgete; Morrot, Alexandre; Nunes, Marise Pinheiro; Freire-de-Lima, Celio Geraldo; Decote-Ricardo, Debora (Frontiers in Immunology, 2017)
Trypanosoma cruzi is an obligatory intracellular protozoan parasite, and it is the etiological agent of Chagas’ disease that is endemic in the Americas. In addition to humans, a wide spectrum of mammals can be infected by T. cruzi, including dogs. Dogs develop acute and chronic disease, similar to human infection. T. cruzi can infect almost all cell types and after cell invasion, the metacyclics trypomastigotes localize in the cytoplasm, where they transform into amastigotes, the replicative form of T. cruzi in mammals. After amastigote multiplication and differentiation, parasites lyse host cells and spread through the body by blood circulation. In this work, we evaluated the in vitro ability of T. cruzi to infect a canine macrophage cell line DH82 compared with RAW264.7, a murine tissue culture macrophage. Our results have shown that the T. cruzi is able to infect, replicate and differentiate in DH82 cell line. We observed that following treatment with LPS and IFN-γ DH82 cells were more resistant to infection and that resistance was not related reactive oxygen species production in our system. In this study, we also found that DH82 cells became more susceptible to T. cruzi infection when cocultured with apoptotic cells. The analysis of cytokine production has showed elevated levels of the TGF-β, IL-10, and TNF-α produced by T. cruzi-infected canine macrophages. Additionally, we demonstrated a reduced expression of the MHC class II and CD80 by infected DH82 cell line.